Analyzing Project Management Methods in Organizing Sports Events. (December 2020) - Schnitzer, Martin; Kronberger, Kathrin; Bazzanella, Filippo; Wenger, Sebastian
The purpose of this study was to investigate the use and importance of project management (PM) methods in organizing sports events (SEs). Furthermore, the study analyzed differences in usage and importance of PM methods in relation to the type of SE. Finally, reasons for and obstacles to the implementation of PM methods in organizing SEs were identified. To assess the research questions, a quantitative survey ( n = 78) and a focus group discussion ( n = 5) were carried out. The results showed that PM methods were employed for SEs with higher usage and importance rates in large compared with small SEs. Requirements by event stakeholders, knowledge transfer, confidence building, progress control, and justification as well as opportunities to save money by introducing an improved planning process were identified as the main reasons for using PM in the organization of SEs. This study is the first work to provide an overview of the usage of specific PM methods in organizing SEs.